THREE—DIMENSIONAL RECONSTRUCTION AND VIRTUAL ENDOSCOPY OF MALIGNANT TUMORS OF THE LARYNGOPHARYNX AND LARYNX - Sokolov, Viktor; Rozhkovska, Galyna; Dorofeeva, Tamara; Tsvihovsky, Viacheslav; Arbatska, Anastasia (European Science, 2025)
Virtual multislice computed tomography (MSCT) endoscopy enables detailed identification of the anatomical and topographic characteristics of the larynx and laryngopharynx, precise localization and sizing of tumors, and assessment of surrounding bony, cart